Low Level Laser Versus Transcutaneous Electrical Nerve Stimulationon Post Herpetic Neuralgia - Marwa Lotfy Mohamed Ahmed, Wafaa Hussein Borhan, Maha Hussein Ragaia, Hussein Gamal Hussein Mogahed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Post herpetic neuralgia (PHN), a common neuropathic pain syndrome, usually occurs in patients with acute herpes zoster after resolving skin eruption. Persistent severe pain has a huge impact on a patient’s physical function, mental health, and social communication ability, and also places a heavy burden on patients’ families and on society. Objective: The current study was conducted to compare the efficacy of low level laser therapy (LLLT) versus transcutaneous electrical nerve stimulation (TENS) in the treatment of post-herpetic neuralgia Subjects and Methods: Fifty patients suffering from pain post herpetic neuralgia .Their ages ranged from 40 to 80 years.They were selected randomly from outpatient clinic in Deraya university referred by dermatologist then divided into two equal groups. Group (A) composed of 25 patients with post herpetic neuralgia and they received low level laser therapy LLLT in addition to traditional medical treatment and Group (B) composed of 25 patients with post herpetic neuralgia and they received Transcutaneous electrical nerve stimulation in addition to traditional medical treatment .Both modalities were applied once daily, 3 times a week for 20 minutes for 4 successive weeks. Visual analog scale (VAS) and pain pressure threshold (PPT) had been assessed before and after interventions. Results: There was a significant decrease in VAS and a significant increase in PPT post treatment compared with that pre treatment in group A and B (p > 0.001). The percent of change in VAS and PPT in group A was 88.97 and 522.22% respectively, while that in group B was 82.39 and 462.79% respectively. Conclusion: Both LLLT and TENS were effective improving the post-herpetic neuralgia but LLLT was more effective. Keywords: Low level laser therapy, transcutaneous electrical nerve stimulation, post herpetic neuralgia, visual analog scale and pain pressure threshold